2016
DOI: 10.1002/jso.24401
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of patient and provider perception of “cure” as a goal of cancer surgery

Abstract: Patients with resectable lung and gastrointestinal cancers have more optimistic perceptions about the outcomes of an upcoming surgery than their surgeons, even in a setting of good communication and shared decision-making. J. Surg. Oncol. 2016;114:677-683. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…All 32 included publications had a cross‐sectional study design, 11 of which derived their patient population from previous cohort studies, or from the control group of a randomized trial. Twenty of the 32 studies were published after 2010, 11 between 2000 and 2010, and one in 1989.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 32 included publications had a cross‐sectional study design, 11 of which derived their patient population from previous cohort studies, or from the control group of a randomized trial. Twenty of the 32 studies were published after 2010, 11 between 2000 and 2010, and one in 1989.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared SDM among patients and among surgeons using the CPS questionnaire. Eighty‐nine of 204 surgeons (43·6 per cent) perceived the decision‐making process as SDM.…”
Section: Resultsmentioning
confidence: 99%
“…By reporting data both on individual specific metrics, as well as composite TOO, patients are better equipped to frame expectations around their short‐ and long‐term care. Data from our own group have demonstrated that patients tend to be overly optimistic relative to expectations around both short‐ and long‐term outcomes compared with their surgeons 19,20 . Specifically, compared with surgeons, patients tend to underestimate the risk of perioperative complications, while overestimating the potential therapeutic benefit of surgery 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Data from our own group have demonstrated that patients tend to be overly optimistic relative to expectations around both short‐ and long‐term outcomes compared with their surgeons 19,20 . Specifically, compared with surgeons, patients tend to underestimate the risk of perioperative complications, while overestimating the potential therapeutic benefit of surgery 20 . Providing patients data on composite measures such as textbook outcome and TOO may facilitate more “realistic” conversations and help frame expectations around complex surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, perioperative data evaluating the effects of patient expectations on outcomes predominantly include benign surgical indications and are highly heterogeneous in origin and conclusions 10‐12 . Contemporary studies have qualitatively analyzed various aspects of surgeon‐patient communication, such as surgeon and patient buy‐in, 13 incorporation of quality of life considerations into discussions, 14 completeness of information relayed, 15 and surgeon‐led end‐of‐life discussions 4 . Communication and decision tools have been produced as a result 15‐19 .…”
Section: Introductionmentioning
confidence: 99%